Absolute Bioavailability and Pharmacokinetic Comparability of Sirukumab Following Subcutaneous Administration by a Prefilled Syringe or an Autoinjector. Issue 6 (3rd January 2017) - Zhuang, Y.; de Vries, D. E.; Marciniak, S. J.; Liu, H.; Zhou, H.; Davis, H. M.; Leon, F.; Raible, D.; Xu, Z.
Abstract: This phase 1, randomized, open‐label study assessed the absolute bioavailability and pharmacokinetic comparability of sirukumab, a human anti–interleukin‐6 monoclonal antibody, following subcutaneous (SC) administration via Prefilled Syringe‐UltraSafe Passive® Delivery System (PFS‐U) or Prefilled Syringe‐SmartJect® Autoinjector (PFS‐AI; Janssen Research & Development, LLC, Spring House, Pennsylvania). A total of 144 healthy male subjects were randomized to 5 single‐dose treatment groups: sirukumab 50 mg and 100 mg (each by PFS‐U and PFS‐AI) and sirukumab 100 mg intravenous (IV) infusion. Pharmacokinetic parameters were calculated using noncompartmental analysis. Following SC administration, maximum serum concentrations (Cmax ) and area under the concentration‐vs‐time curve (AUC) increased in an approximately dose‐proportional manner. Median time to reach Cmax was 5 days, and mean half‐life ranged from 16 to 19 days. Mean absolute bioavailability of sirukumab by PFS‐AI and PFS‐U, respectively, was estimated at 92.4% and 81.4% with 100 mg and 88.4% and 94.7% with 50 mg. Ratios of geometric means (90% confidence intervals) of Cmax and AUC0‐77d for PFS‐AI:PFS‐U were 1.13 (1.03, 1.25) and 1.14 (1.05, 1.24), respectively, indicating comparable systemic exposures of sirukumab following a single 100‐mg SC dose by PFS‐U or PFS‐AI. The incidence of antibodies to sirukumab was low (1.4%). No new safety concerns associated with sirukumab were identified at either dose.